Dietary patterns associated with colorectal cancer risk in the Malaysian population: a case–control study with exploratory factor and regression analysis - Ainaa Almarrdhiyah, Abd Rashid; Lydiatul, Shima Ashari; Nor Hamizah, Shafiee; Raja Affendi, Raja Ali *; Lee, Yeong Yeh; Mohd Razif, Shahril; Hamid Jan, Jan Mohamed (BMC (Springer Nature), 2023)
Background: Studies on the relationship between diet and colorectal cancer (CRC) risk using single food or nutrient approach are widely conducted as opposed to dietary pattern approach. Therefore, this study aimed to determine the major dietary patterns and their association with CRC risk among Malaysians.